Analysis Of The Pattern Of Education For Persons With Disabilities In Law Number 20 Of 2003 Concerning The National Education System - Zamrony ABDUSSAMAD; Sudarsono SUDARSONO; Imam KOESWAHYONO; Istislam ISTISLAM (International Journal of Environmental, Sustainability, and Social Science, 2022)
Inclusive education has many different meanings and interpretations. There is still some uncertainty about the difference between inclusive and special education for individuals with disabilities, sometimes known as special schools (SLB). Meanwhile, the term inclusive education is not known in the National Education System Law, which uses the term "special education and special services," which is explained in Article 32 of Law No. 20 of 2003 concerning the National Education System: (i) Special education is education for students who have difficulty levels. Participating in the learning process due to physical, emotional, mental, social, intellectual potential and special talents. (ii) Special service education is education for students in remote or underdeveloped areas, remote indigenous peoples, and experiencing natural disasters, social disasters, and economically disadvantaged. This research's problem approaches are conceptual, statutory, and case approaches. Based on this, we found that the ambiguity of norms affects the pattern of providing education for persons with disabilities, namely the dualism of providing education for persons with disabilities with a special and inclusive approach which has an impact on legal uncertainty in norms, concepts and implementation.